Navigating Financial Uncertainty: Hospital Cost Strategies During the Initial COVID-19 Outbreak in Indonesia - Ningsih, Sri; Machin, Abdulloh; Harymawan, Iman; Fitriani, Nurul; Ramadhany, Prima (Jati: Jurnal Akuntansi Terapan Indonesia, 2025)
The COVID-19 pandemic revealed fundamental weaknesses in healthcare financing systems, particularly in developing countries like Indonesia. Public hospitals faced significant challenges in sustaining operations due to changes in reimbursement policies and the increasing complexity of services, while simultaneously relying on government funding. The absence of a stable and adaptive payment mechanism during the pandemic led to prolonged financial uncertainty. This study examines the financial strategies public hospitals adopt to maintain operational continuity amid changes in the reimbursement scheme for COVID-19 patients. The research was conducted at Universitas Airlangga Hospital using 547 COVID-19 patient claim records and interviews with the hospital's financial manager, which were analyzed through descriptive methods. The findings indicate that hospitals utilized strategies based on internal resources, such as cost reallocation, improved coordination, and integration between medical service units and financial departments, in response to external regulatory pressures. Collaboration between clinical and administrative teams improved cost control and operational resilience during the transition period of payment systems. This study emphasizes the importance of utilizing internal hospital capabilities, including financial systems, governance structures, and interdepartmental synergy, in dealing with policy uncertainty. Hospitals needs to develop responsive and forward-looking financial strategies to cope with public health crises. For policymakers, the findings highlight the urgency of designing reimbursement systems that are responsive, transparent, and based on hospitals' actual needs and the sustainability of healthcare services in the future.